2019
DOI: 10.5114/aoms.2018.72566
|View full text |Cite
|
Sign up to set email alerts
|

Topical morphine for treatment of cancer-related painful mucosal and cutaneous lesions: a double-blind, placebo-controlled cross-over clinical trial

Abstract: Topical morphine for treatment of cancer-related painful mucosal and cutaneous lesions: a double-blind, placebo-controlled cross-over clinical trial Aleksandra Ciałkowska-Rysz, Tomasz Dzierżanowski A b s t r a c t Introduction: Painful mucosal and cutaneous lesions are often less responsive or even refractory to systemic opioid analgesics. There is evidence suggesting that the effectiveness of topical morphine be restricted to inflammatory pain. The studied groups were small and the observation period relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
0
12
0
3
Order By: Relevance
“…In case of local pain, a nerve block might diminish pain. In smaller wounds, application of morphine gel can be considered [125,126].…”
Section: Best Supportive Carementioning
confidence: 99%
“…In case of local pain, a nerve block might diminish pain. In smaller wounds, application of morphine gel can be considered [125,126].…”
Section: Best Supportive Carementioning
confidence: 99%
“…We selected morphine because it has proven to be an effective analgesic agent and researchers are increasingly studying its topical applications to treat inflammation and pain in palliative care settings. 41,42 Morphine administration was modeled accurately by the base model across both the IV and transdermal route of administration, as measured by AAFE <3.0 for AUC0t and AAFE <1.5 for C max , t max across both experimental profiles. The higher optimized permeability value (0.16 cm/h) is expected given that the skin at the application site was de-epithelialized prior to compound administration.…”
Section: Dovepressmentioning
confidence: 99%
“…44 More recently, Ciałkowska-Rysz et al found self-administered topical morphine to be a highly effective and safe medication for treating mucosal and skin lesions in palliative cancer patients, providing sustained pain relief for over 28 days. 41 The studies discussed above also suggest that the transdermal route is associated with a higher patient compliance as it offers evasive dosing, the possibility of self-administration, and flexibility in adjusting dosing regimen to experience rapid and long-lasting pain relief, hence the interest in accurate modeling and simulation.…”
Section: Dovepressmentioning
confidence: 99%
“…One controlled trial found a strong trend supporting the efficacy of a gel containing baclofen 10 mg, amitriptyline 40 mg, and ketamine 20 mg for neuropathic symptoms associated with chemotherapy‐induced peripheral neuropathy and another small study favored menthol 1% in cancer‐related neuropathic pain . Topical morphine is used by some specialists in palliative care for pain associated with pressure ulcers or mucosal lesions …”
Section: Multipurpose Adjuvant Analgesicsmentioning
confidence: 99%